Determining the Role of Exclusive Breastfeeding and Nutritional Status in Stunting Prevention: A Literature Review - Erwani, Erwani; Susanti, Dewi; Doni, Alsri Windra; Yuda, Rahmi Andrita; Yanti, Meyi (Poltekkes Kemenkes Palu, 2023)
Stunting among children is a serious global concern including Indonesia since it has a negative impact on children's growth and development. Globally, more than 148 million children are affected by stunting. In Indonesia, the prevalence of stunting was 21.6% in 2022, which reflected a serious problem that needs to be addressed. This study aims to explore the correlation between exclusive breastfeeding, nutritional status and stunting among under-five children in Indonesia. The current study explored the correlation between exclusive breastfeeding (EBF) and nutritional status with the incidence of stunting among under-five. The inclusion criteria consisted of original articles, open access, written in English/Indonesian, 2020-2023, discussed EBF, nutritional status, and stunting. Databases involved ScienceDirect, PubMed, BMC journals, Google Scholar. Article selection used keywords and MeSH, and the results were presented in a PRISMA diagram. It was conducted an analysis of 10 articles, which were grouped in a matrix based on author, year, journal name, title, methods, and results. The results revealed that exclusive breastfeeding practice was correlated with a 3.1-fold reduction in the risk of stunting (CI 95%=1.5–6.4). Factors such as good nutrition and breastfeeding for at least 6 months provided protection from the risk of stunting. In conclusion, exclusive breastfeeding and good nutritional status were required, along with strengthening education and promotion regarding nutritional fulfilment patterns. Integration of the study findings should be made in child health guidelines, which may further guide policy and practice, support concrete steps to reduce the prevalence of stunting, and ensure optimal growth of children. Recommendations in this study include improvement in maternal education, nutritional support, and child health policy advocacy. For next steps, in-depth research is needed to evaluate the impact of specific nutritional interventions, understand the social and cultural factors that influence nutritional practices, and assess the effectiveness of cross-sector programs in reducing the prevalence of stunting.